Effect of the COVID-19 pandemic on the behavior of the Peruvian economy, 2020 - Olivera Cáceres , Jesús Amadeo (2021)
The COVID-19 pandemic generated severe losses in the world’s economies, which caused a serious impact on the Peruvian economy, in addition to a future characterized by uncertainty. The purpose of the research was to analyze the effect of the COVID-19 pandemic on the behavior of the Peruvian economy, corresponding to the period 2020. The methodology was based on a quantitative approach, of a basic type, non-experimental design, of a descriptive documentary level. Finally, it was established that the COVID-19 pandemic had a negative effect on the behavior of the Peruvian economy, as negative descending values were found in the Gross Domestic Product (GDP) (-11.1 %); imports (-14.9 %); global supply and demand (-12 %); domestic demand (-10.1 %); and exports (-19 %). The drop in GDP to -11.1% in 2020 represented a loss of more than 131 billion soles, which was similar to more than 1.2 billion soles per day. To mitigate the effect of the COVID-19 pandemic on the economy, the Peruvian State carried out economic reactivation by making the conditions for companies to resume their activities more flexible.